Alkali Ions Pre‐Intercalated Layered MnO2 Nanosheet for Zinc‐Ions Storage. Issue 31 (26th June 2021) - Liu, Liyuan; Wu, Yih‐Chyng; Huang, Liang; Liu, Kaisi; Duployer, Benjamin; Rozier, Patrick; Taberna, Pierre‐Louis; Simon, Patrice
Abstract: Recently, rechargeable zinc‐ion batteries in mild acidic electrolytes have attracted considerable research interest as a result of their high sustainability, safety, and low cost. However, the use of conventional Zn‐ion storage materials is hindered by insufficient specific capacity, sluggish reaction kinetics, or poor cycle life. Here, these limitations are addressed by pre‐intercalating alkali ions and water crystals into layered δ‐MnO2 (birnessite) to prepare K0.27 MnO2 ·0.54H2 O (KMO) and Na0.55 Mn2 O4 ·1.5H2 O with ultrathin nanosheet morphology via a rapid molten salt method. In these materials, alkali ions and water crystals act as pillars to stabilize the layered structures, which can enable rapid diffusion of cations in the KMO structure, resulting in high power capability (90 mAh g −1 at 10 C) and good cycling stability. Furthermore, electrochemical quartz crystal microbalance measurements shed light on the charge storage mechanism of KMO in an aqueous Zn‐ion battery which, combined together with in‐operando X‐ray diffraction techniques, suggests that the charge storage process is dominated by the (de)intercalation of H3 O + with further dissolution–precipitation of Zn4 (OH)6 (SO4 )·5H2 O solid product on the KMO surface during cycling. Abstract : A molten salt‐prepared K0.27 MnO2 ·0.54H2 O cathode achieves a high capacity of 288 mAh g −1 at C/3 and high‐power capability (88 mAh g −1 at 10 C) in an aqueous Zn‐ion battery configuration. The combination of in situ XRD and electrochemical quartz crystal microbalance reveal a charge storage process dominated by (de)intercalation of (hydrated) protons with further dissolution–precipitation of Zn4 (OH)6 (SO4 )·5H2 O.